2022
DOI: 10.1021/acs.jpcc.1c08739
|View full text |Cite
|
Sign up to set email alerts
|

Selective Oxidation of Methane to Formaldehyde over a Silica-Supported Cobalt Single-Atom Catalyst

Abstract: Catalytic oxidation of methane to formaldehyde and methanol has attracted attention because of its advantage in energy efficiency over the conventional multistep reaction process involving endothermic steam reforming of CH 4 ; however, it is challenging to selectively obtain the partial oxidation products in the direct oxidation of CH 4 . In the present study, Co/SiO 2 with various Co loadings was tested for the CH 4 /O 2 /H 2 O gas flow reaction. As a result, Co/SiO 2 with a low loading of ≤0.1 wt % showed hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…• Al 2 O 3 [321] • Carbon/Graphene [59,177,236,353,423] • Carbon nitride [424,425] • MnO 2 [424] • MoS 2 [426] • N 3 P 1 site [427] • SiO 2 [426,428] • TiO 2 [426] • ZnO [361] • ALD [423] • Ball milling [353] • Electrochemical method [425] • Freeze-drying method [59] • Mass-selected soft-landing [236] • Pyrolysis-assisted method [211,426,427,429,430] • Redox-driven hydrolysis [431] • Sol-gel method [361] • Thermal emitting strategy [214] • Thermal polymerization [424] • Wet impregnation [321,426,428] ,…”
Section: Comentioning
confidence: 99%
See 1 more Smart Citation
“…• Al 2 O 3 [321] • Carbon/Graphene [59,177,236,353,423] • Carbon nitride [424,425] • MnO 2 [424] • MoS 2 [426] • N 3 P 1 site [427] • SiO 2 [426,428] • TiO 2 [426] • ZnO [361] • ALD [423] • Ball milling [353] • Electrochemical method [425] • Freeze-drying method [59] • Mass-selected soft-landing [236] • Pyrolysis-assisted method [211,426,427,429,430] • Redox-driven hydrolysis [431] • Sol-gel method [361] • Thermal emitting strategy [214] • Thermal polymerization [424] • Wet impregnation [321,426,428] ,…”
Section: Comentioning
confidence: 99%
“…• Benzene oxidation [321] • CO 2 RR [351,429] • Fenton-like reaction [424] • HER [425] • Hydrogenation [347,353,423,427] • Methane oxidation [428] • Nitrogen reduction [347] • OER [236,426] • ORR [214,236,361] • Toluene oxidation [431] to butadiene as displayed in Fig. 19(c).…”
Section: Comentioning
confidence: 99%
“…For the synthesis of CH 2 O, various methods were suggested comprising direct CO and CO 2 hydrogenation [4,5], selective oxidation of methane [6] or higher hydrocarbons such as propane or propene [7]. However, these routes still have not found an industrial application, and on a large scale, CH 2 O is nowadays still manufactured from methanol (CH 3 OH) by selective vapor-phase oxidation (Eq.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Since then, SACs have been utilized to catalyse several reactions such as water oxidation, [5][6][7] CO 2 reduction [8][9][10] and hydrogenation, [11,12] oxygen reduction, [13][14][15] hydrogen evolution, [7,[15][16][17][18] among others. [7,[19][20][21][22][23] Zhang and co-workers also synthesized a mixed gold and palladium SAC, which was supported on ion exchange resins and used to catalyse Ullmann reaction [24] of aryl halides in an aqueous media. [25] The authors reported that the synthesized SAC possessed high yield and selectivity; both can be tuned with the levels of Au and Pd in the SAC.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of single atom catalysts (SACs) was first introduced by Zhang and co‐workers in 2011, where a single atomic layer of platinum was incorporated into an iron oxide support [4] . Since then, SACs have been utilized to catalyse several reactions such as water oxidation, [5–7] CO 2 reduction [8–10] and hydrogenation, [11,12] oxygen reduction, [13–15] hydrogen evolution, [7,15–18] among others [7,19–23] . Zhang and co‐workers also synthesized a mixed gold and palladium SAC, which was supported on ion exchange resins and used to catalyse Ullmann reaction [24] of aryl halides in an aqueous media [25] .…”
Section: Introductionmentioning
confidence: 99%